جهود ابن القيم في علوم القرآن من خلال التفسير القيم - سعداني, شفاء (University of Eloued جامعة الوادي, 2020)
"تسلط الدراسة الضوء على جهود عالم كبير من علماء الإسلام ؛العلامة شمس الدين محمد بن أبي بكر الزرعي الدمشقي المشهور بابن القيم الجوزية (ت 751 ه)في علوم القرآن الكريم ،وإعتمدت الدراسة في ذلك على التفسير القيم كنموذج لبيان جهود الإمام -رحمه الله -،فجاءت تحت عنوان""جهود ابن القيم في علوم القرآن من خلال تفسيره القيم "". إنقسمت الدراسة لشقين :شق نظري وشق تطبيقي . احتوى الشق النظري على مبحثين ،مبحث أول :وهو عبارة عن مدخل لعلوم القرآن ،وبحث ثاني تعريفي موجز بالإمام ابن القيم والتفسير القيم ،ومنهج ابن القيم في التفسير. وفي الجانب التطبيقي جمعت الدراسة أهم علوم القرآن التي إعتمدها الإمام ابن القيم في تفسيره ،والواردة في التفسير القيم ،وجاءت على ثلاث مباحث مقسمة حسب درجة التناول من الأكثر إلى الأقل." The study highlights the efforts of a prominent Islamic scholar, namely the distinguished Shams al-Dīn Mohammad Bin Abi Bakr al-Zurii al-Dimashqī, who is known as Ibn Qayyim al-Jawziyya (born in 751 Hijri) in the Holy Qur'an Sciences. The study relies on the ""Valuable Exegesis"" as a case to underline the Imam's efforts - God bless him - and entitled: The researcher breaks up the study into two sections: a theoretical one, which represents an introduction to Qur'an Sciences. The second section is a brief biography of the Imam Ibn Qayyim, exegesis of the methodology he opted for in the exegesis. The practical part gathers the most significant Qur'an Sciences adopted by the Imam Ibn Qayyim included in the ""Valuable Exegesis"" and classified under three sections according to the degree of reception, from the most to least.
مذكرة ماستر تخصص تفسير وعلوم قرآن
Keywords: جهود ابن القيم في علوم القرآن من خلال التفسير القيم; Ibn Qayyim efforts in Qur'an Sciences through the "Valuable Exegesis.